Efficacy and Safety of Direct-Acting Antiviral Therapy in Patients With Chronic Hepatitis C Virus Infection: A Real-World Single-Center Experience in Tianjin, China - Xia, Huan; Lu, Chengzhen; Wang, Yin; Zaongo, Silvere D.; Hu, Yue; Wu, Yue; Yan, Zhongfang; Ma, Ping (Frontiers in Pharmacology, 2020)
Objective: Towards the limited real-world data concerning the treatment response to brand direct-acting antiviral agents (DAAs) therapy, we proposed to evaluated the efficacy and safety of DAAs for the treatment of chronic hepatitis C (HCV) in mainland China. Methods: In this retrospective, single-center, cohort study, all HCV-infected adult patients treated with brand DAA drugs covered by Tianjin local health insurance (Apr 2018 - Aug 2019) and responding to other specific inclusion criteria were recruited. The five available DAA regimens included sofosbuvir + ribavirin (SOF + RBV), elbasvir/grazoprevir (EBR/GZR), ombitasvir/paritaprevir/ritonavir/dasabuvir (OBV/PTV/r/DSV) ± RBV, daclatasvir + asunaprevir (DCV + ASV), and SOF + DCV ± RBV. Demographic, virologic, clinical, and adverse effects data obtained during and after DAAs treatment were collected. We evaluated the rate of sustained virological response at 12 weeks post-treatment (SVR12), the incidence of adverse effects, and assessed the factors associated with SVR12. Results: 494 patients finished the treatment and completed the 12-week post-treatment follow-up. The overall SVR12 rate was estimated at 96.96%. SVR rates greater than 95% were achieved in most of the HCV genotypes with the exception of GT1a (0%), GT3a (93.33%), and GT3b (88.24%). SVR12 for patients treated with DCV + ASV, EBR/GZR, OBV/PTV/r/DSV ± RBV, SOF + DCV ± RBV, and SOF + RBV for 12 or 24 weeks was 86.67%, 100%, 98.11%, 97.56%, and 95.06%, respectively. Subjects with compensated cirrhosis (92.73%) and prior treatment experience (77.78%) had significantly lower SVR rates when compared to chronic hepatitis C (98.15%) and treatment-naive (97.69%) groups. In Tianjin, the available DAA regimens were generally well-tolerated, and not a single serious adverse event was reported. Conclusion: In this large real-life single-center HCV cohort from China, oral DAAs were highly effective and well-tolerated. Further and larger-scale studies are needed to evaluate their clinical safety and efficacy.